High-adhesion polyethylene wax composite diaphragm and application thereof in lithium battery
By adding specific components to the polyethylene wax coating of the lithium-ion battery separator, forming a network structure and hydrogen bond, combined with the improvement of the ceramic coating, the problem of poor interface compatibility between the polyethylene wax coating and other coatings or base films in the separator is solved, and the adhesion and durability of the separator are significantly improved.
Patent Information
- Application Number
- CN202411938140.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-26
AI Technical Summary
In the existing lithium-ion battery separators, the interface compatibility between the polyethylene wax coating and other coatings or base films is poor, resulting in insufficient adhesion, which is easy to peel off or crack during charging and discharge, resulting in short circuit inside the battery.
By adding ethylene-vinyl acetate copolymer, reinforcement fibers, interface compatibilizers and polymers containing carboxyl, hydroxyl or amine groups to the polyethylene wax coating, network structure and hydrogen bonds are formed, the bond strength between layers is improved, and zirconia powder and styrene acrylic emulsion are added to the ceramic coating to improve mechanical strength and water resistance.
The adhesion between the polyethylene wax coating and other coatings or base films is significantly improved, the peeling phenomenon is reduced, and the durability and thermal stability of the membrane are improved.
Smart Images

Figure BDA0005211982840000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium battery separators, and in particular to a high-adhesive polyethylene wax composite separator and application thereof in lithium batteries. Background Art
[0002] In the construction of lithium batteries, the diaphragm is a key component that plays an important role in isolating the positive and negative electrodes, preventing short circuits, and ensuring the normal transmission of lithium ions. Among them, the polyethylene wax composite diaphragm, as a new type of high-performance diaphragm material, has attracted much attention. The polyethylene wax composite diaphragm exhibits excellent heat resistance and chemical corrosion resistance, and can maintain stable performance under high temperature and harsh environments, thereby ensuring the safety and reliability of lithium batteries in various application scenarios.
[0003] In the related art, a preparation method for a lithium-ion battery diaphragm is disclosed, comprising the following steps: polyethylene wax particles and water are mixed evenly to obtain a polyethylene wax aqueous dispersion. The polyethylene wax aqueous dispersion, polyacrylic acid, and sodium carboxymethyl cellulose are stirred and mixed evenly, and water is added to adjust the solid content to obtain a polyethylene wax emulsion. Ceramic particles, sodium carboxymethyl cellulose, polyacrylic acid, and styrene acrylic emulsion are stirred and mixed evenly, and water is added to adjust the solid content to obtain a ceramic slurry. The polyethylene wax emulsion is coated on both sides of a porous substrate, dried, and then subjected to surface functional treatment. The polyethylene wax emulsion forms an organic polyethylene wax coating on the surface of the polyethylene porous base film, and the thickness of the organic polyethylene wax coating is 1 μm, thereby obtaining a polyethylene porous base film with an organic polyethylene wax coating. The ceramic slurry is coated on the surface of the organic polyethylene wax coating after the surface functional treatment, dried, and the ceramic slurry forms a ceramic coating on the surface of the organic polyethylene wax coating, and the thickness of the ceramic coating is 2 μm, thereby obtaining a lithium-ion battery diaphragm.
[0004] For the above-mentioned lithium-ion battery separator, if the interface compatibility between the polyethylene wax coating, the ceramic coating and the polyethylene porous base film is poor, the interaction force between them will be weakened, and the adhesion between the polyethylene wax coating and the ceramic coating and the polyethylene porous base film after coating may be insufficient. During the battery charging and discharging process, due to changes in temperature and pressure, the coating may peel off or crack, resulting in an internal short circuit in the battery. Therefore, how to reduce the peeling of the polyethylene wax coating and other coatings or base films in the above-mentioned lithium-ion battery separator, thereby improving the durability of the separator, is a problem that needs to be studied at present. Summary of the invention
[0005] In order to improve the durability of the diaphragm, the present application provides a high-adhesion polyethylene wax composite diaphragm and its application in lithium batteries.
[0006] In the first aspect, the present application provides a high-adhesive polyethylene wax composite diaphragm, which adopts the following technical solution:
[0007] A high-adhesive polyethylene wax composite diaphragm comprises a polyethylene wax coating, a ceramic coating and a polyethylene porous base film. The polyethylene wax coating comprises the following raw materials in parts by weight: 50-70 parts of polyethylene wax, 5-15 parts of ethylene-vinyl acetate copolymer, 10-25 parts of reinforcing fiber, 0.5-2 parts of flame retardant, 0.5-2 parts of antioxidant, 2-4 parts of interface compatibilizer, and 2-4 parts of polymer containing carboxyl, hydroxyl or amine groups.
[0008] By adopting the above technical scheme, the molecular chain of polyethylene wax forms a network structure in the coating, which helps to enhance the cohesion and adhesion of the coating. The vinyl acetate part in the molecular chain of ethylene-vinyl acetate copolymer provides polar groups, which helps to form hydrogen bonds with polymers containing carboxyl, hydroxyl or amine groups, thereby improving the bonding strength between layers. The reinforcing fiber can form a three-dimensional network structure in the coating, increasing the cohesion and anti-peeling properties of the coating. The interfacial compatibilizer acts as a bridge between the coating and other materials, which can reduce the interfacial tension between the two, improve compatibility and bonding strength. Carboxyl, hydroxyl and amine groups are all polar groups that can interact with polar groups in adjacent materials to form strong chemical bonds. Therefore, under the joint action of polyethylene wax, ethylene-vinyl acetate copolymer, reinforcing fiber, interfacial compatibilizer and polymers containing carboxyl, hydroxyl or amine groups, it helps to significantly improve the bonding force between the polyethylene wax coating and other coatings or base films, reducing the possibility of peeling, thereby improving the durability of the diaphragm.
[0009] In a specific embodiment, the interfacial compatibilizer includes at least one of polyethylene terephthalate, polycaprolactone or polyamide elastomer.
[0010] By adopting the above technical scheme, the above three components all have good compatibility with polyethylene wax, and have shorter chain lengths and higher activity, and can form a bridge between polyethylene wax and inorganic ceramics or polyethylene porous base membranes, thereby enhancing the interaction between them and helping to form a good interface bonding.
[0011] In a specific embodiment, the polyethylene wax coating further comprises nano silicon dioxide or nano aluminum oxide.
[0012] By adopting the above technical solution, nano-silicon dioxide and nano-alumina can improve the thermal deformation temperature and thermal stability of the polyethylene wax coating, preventing the diaphragm from deforming or performance degradation in a high temperature environment. The small particle size of nano-silicon dioxide and nano-alumina can be filled into the tiny pores of the polyethylene wax coating, improving the barrier performance of the diaphragm to gas and moisture, protecting the internal materials from erosion by the external environment, thereby further improving the durability of the diaphragm.
[0013] In a specific embodiment, the polymer containing carboxyl, hydroxyl or amine groups is any one of polyacrylic acid, polymethacrylic acid, polyvinyl alcohol or polyethyleneimine.
[0014] By adopting the above technical solution, these polymers can form hydrogen bonds or ionic bonds with other components in the polyethylene wax coating and the base film, thereby significantly improving the adhesion and interlayer bonding strength of the separator. Moreover, these polymers have good fluidity and film-forming properties, which can improve the processing performance of the polyethylene wax coating, making it easier to spread and uniformly form a film during the preparation process.
[0015] In a specific embodiment, the reinforcing fibers are cellulose nanofibers.
[0016] By adopting the above technical solution, cellulose nanofibers have excellent mechanical properties and high specific surface area, which can effectively enhance the tensile strength, tear strength and puncture resistance of the composite diaphragm, so that it can withstand greater mechanical stress and improve safety in applications such as batteries. Cellulose nanofibers have good thermal stability and can increase the thermal deformation temperature of the composite diaphragm to a certain extent, prevent deformation in high temperature environments, and maintain the integrity and performance of the diaphragm.
[0017] In a specific embodiment, the flame retardant is ammonium polyphosphate or melamine.
[0018] By adopting the above technical solution, both ammonium polyphosphate and melamine can improve the flame retardant properties of the polyethylene wax composite diaphragm. Moreover, the thermal stability and chemical stability of the polyethylene wax composite diaphragm can be improved, so that it can maintain better performance under high temperature or harsh environment.
[0019] In a specific embodiment, the antioxidant is a phosphite.
[0020] By adopting the above technical solution, phosphite can not only effectively remove or reduce the active oxygen generated by polyethylene wax during processing, storage and use, thereby slowing down the oxidative degradation rate of the material, but also improve the hydrolysis resistance and thermal stability of the polyethylene wax coating, thereby extending the service life of the diaphragm.
[0021] In a specific embodiment, the ceramic coating comprises the following raw materials in parts by weight: 5-12 parts of zirconium oxide powder, 1-2 parts of sodium carboxymethyl cellulose, 3-5 parts of polyacrylic acid liquid, and 7-10 parts of styrene acrylic emulsion.
[0022] By adopting the above technical scheme, zirconium oxide has high hardness and wear resistance, which can improve the mechanical strength and durability of the diaphragm. Styrene acrylic emulsion helps to improve the water resistance and film-forming properties of the ceramic coating, ensuring that the coating can still maintain good performance in a humid environment. Polyacrylic acid liquid enables the ceramic coating to better adapt to the deformation of the diaphragm during use. Sodium carboxymethyl cellulose has good adhesion and dispersibility, which can ensure that the components in the ceramic slurry are evenly mixed and tightly bonded to the surface of the diaphragm. This helps to form a uniform and dense ceramic coating and improve the barrier properties of the diaphragm. Therefore, the above ceramic coating can better resist physical damage during use and extend its service life. Moreover, it also has excellent thermal stability and thermal conductivity, which can effectively reduce the thermal expansion coefficient of the diaphragm in a high temperature environment and improve the heat conduction efficiency.
[0023] In a second aspect, the present application provides a method for preparing a high-adhesive polyethylene wax composite diaphragm, using the following technical solution:
[0024] A method for preparing a high-adhesive polyethylene wax composite diaphragm comprises the following steps:
[0025] Adding polyethylene wax and ethylene-vinyl acetate copolymer into xylene, heating until dissolved, adding reinforcing fiber, flame retardant, antioxidant, interface compatibilizer and polymer containing carboxyl group, hydroxyl group or amine group, mixing evenly, to obtain polyethylene wax coating liquid;
[0026] Applying the polyethylene wax coating liquid on both sides of the polyethylene porous base film, drying, and forming a polyethylene wax coating by the polyethylene wax coating liquid;
[0027] The ceramic slurry is coated on the surface of the polyethylene wax coating and dried, so that the ceramic slurry forms a ceramic coating, and the polyethylene wax coating, the ceramic coating and the polyethylene porous base film form a separator for lithium-ion batteries.
[0028] By adopting the above technical scheme, by introducing ethylene-vinyl acetate copolymer, reinforcing fiber, interface compatibilizer, polymer containing carboxyl, hydroxyl or amine group, the peeling phenomenon of polyethylene wax coating and other coatings or base film in high adhesion polyethylene wax composite diaphragm can be effectively reduced, thereby improving the durability of the diaphragm.
[0029] In a third aspect, the present application provides an application of a high-adhesion polyethylene wax composite diaphragm in a lithium battery, wherein the diaphragm of the lithium battery is a high-adhesion polyethylene wax composite diaphragm.
[0030] In summary, this application has the following beneficial effects:
[0031] 1. The present invention, under the combined action of polyethylene wax, ethylene-vinyl acetate copolymer, reinforcing fiber, interfacial compatibilizer and polymer containing carboxyl, hydroxyl or amine groups, helps to significantly improve the adhesion between the polyethylene wax coating and other coatings or base films, reduces the possibility of peeling, and thus improves the durability of the diaphragm.
[0032] 2. In the present application, nano-silicon dioxide or nano-aluminum oxide is preferably used to improve the thermal stability of the diaphragm.
[0033] 3. The method of the present application can effectively reduce the peeling phenomenon between the polyethylene wax coating and other coatings or base films in the high-adhesion polyethylene wax composite diaphragm, thereby improving the durability of the diaphragm. DETAILED DESCRIPTION
[0034] The present application is further described in detail below in conjunction with embodiments and comparative examples.
[0035] Example
[0036] Example 1
[0037] This embodiment provides a high-adhesive polyethylene wax composite diaphragm, which includes a polyethylene wax coating, a ceramic coating and a polyethylene porous base film.
[0038] Among them, the polyethylene wax coating includes the following raw materials: 60g polyethylene wax, ethylene-vinyl acetate copolymer (Mitsui, brand 410) 10g, cellulose nanofiber (model NFC-31L1) 18g, ammonium polyphosphate 1.2g, phosphite 1.2g, polyethylene glycol terephthalate 3g, polyacrylic acid (liquid, analytical grade) 3g.
[0039] The ceramic coating includes the following raw materials: 8 g of zirconium oxide powder (particle size 5000 mesh), 1.5 g of sodium carboxymethyl cellulose, 4 g of polyacrylic acid liquid (analytical grade), and 8.5 g of styrene-acrylic emulsion.
[0040] This embodiment also provides a method for preparing a high-adhesive polyethylene wax composite diaphragm, comprising the following steps:
[0041] According to the ratio of polyethylene wax coating, polyethylene wax and ethylene-vinyl acetate copolymer are added to xylene, heated to 130°C, and stirred until completely dissolved. Then, cellulose nanofibers, ammonium polyphosphate, phosphite, polyethylene glycol terephthalate and polyacrylic acid are added, and the mixture is stirred at the same temperature until the mixture is evenly mixed to obtain a polyethylene wax coating liquid.
[0042] The polyethylene wax coating liquid is coated on both sides of the polyethylene porous base film and dried to form a polyethylene wax coating with a thickness of 1 μm.
[0043] According to the ratio of the ceramic coating, zirconium oxide powder, sodium carboxymethyl cellulose, polyacrylic acid liquid and styrene acrylic emulsion are mixed uniformly to obtain ceramic slurry.
[0044] The ceramic slurry is coated on the surface of the polyethylene wax coating and dried to form a ceramic coating with a thickness of 2 μm. The polyethylene wax coating, the ceramic coating and the polyethylene porous base film form a separator for lithium-ion batteries.
[0045] Example 2
[0046] The only difference between this embodiment and embodiment 1 is that the polyethylene wax coating includes the following raw materials: 50 g polyethylene wax, 15 g ethylene-vinyl acetate copolymer (Mitsui, brand 410), 25 g cellulose nanofiber (model NFC-31L1), 2 g ammonium polyphosphate, 2 g phosphite, 4 g polyethylene glycol terephthalate, and 4 g polyacrylic acid (liquid, analytical grade).
[0047] Example 3
[0048] The only difference between this embodiment and embodiment 1 is that the polyethylene wax coating includes the following raw materials: polyethylene wax 70g, ethylene-vinyl acetate copolymer (Mitsui, brand 410) 5g, cellulose nanofiber (model NFC-31L1) 10g, ammonium polyphosphate 0.5g, phosphite 0.5g, polyethylene glycol terephthalate 2g, polyacrylic acid (liquid, analytical grade) 2g.
[0049] Example 4
[0050] The only difference between this embodiment and embodiment 1 is that, in the preparation process of the polyethylene wax coating, an equal amount of polycaprolactone is used to replace polyethylene terephthalate.
[0051] Example 5
[0052] The only difference between this embodiment and embodiment 1 is that, in the process of preparing the polyethylene wax coating, an equal amount of polyamide elastomer (Arkema, brand number 2533SN 01) is used to replace polyethylene terephthalate.
[0053] Example 6
[0054] The only difference between this embodiment and embodiment 1 is that, in the preparation process of the polyethylene wax coating, an equal amount of polymethacrylic acid is used to replace polyacrylic acid.
[0055] Example 7
[0056] The only difference between this embodiment and embodiment 1 is that, in the process of preparing the polyethylene wax coating, an equal amount of polyvinyl alcohol is used to replace polyacrylic acid.
[0057] Example 8
[0058] The only difference between this embodiment and embodiment 1 is that, in the preparation process of the polyethylene wax coating, an equal amount of polyethyleneimine is used to replace polyacrylic acid.
[0059] Example 9
[0060] The only difference between this embodiment and embodiment 1 is that, during the preparation of the polyethylene wax coating, an equal amount of melamine is used to replace ammonium polyphosphate.
[0061] Example 10
[0062] The difference between this embodiment and embodiment 1 is that the polyethylene wax coating comprises the following raw materials: 60g polyethylene wax, ethylene-vinyl acetate copolymer (Mitsui, brand 410) 10g, cellulose nanofiber (model NFC-31L1) 18g, ammonium polyphosphate 1.2g, phosphite 1.2g, polyethylene glycol terephthalate 3g, polyacrylic acid (liquid, analytical grade) 3g, nano-silicon dioxide 3g. In the preparation method of the high-adhesive polyethylene wax composite diaphragm: according to the proportion of the polyethylene wax coating, polyethylene wax and ethylene-vinyl acetate copolymer are added to xylene, heated to 130°C, stirred until completely dissolved, and then cellulose nanofiber, ammonium polyphosphate, phosphite, polyethylene glycol terephthalate, polyacrylic acid and nano-silicon dioxide are added, and the mixture is stirred and kept warm until uniformly mixed to obtain a polyethylene wax coating liquid.
[0063] Embodiment 11
[0064] The difference between this embodiment and embodiment 1 is that the polyethylene wax coating comprises the following raw materials: 60g polyethylene wax, 10g ethylene-vinyl acetate copolymer (Mitsui, brand 410), 18g cellulose nanofiber (model NFC-31L1), 1.2g ammonium polyphosphate, 1.2g phosphite, 3g polyethylene glycol terephthalate, 3g polyacrylic acid (liquid, analytical grade), 3g nanoalumina. In the preparation method of the high-adhesive polyethylene wax composite diaphragm: according to the proportion of the polyethylene wax coating, polyethylene wax and ethylene-vinyl acetate copolymer are added to xylene, heated to 130°C, stirred until completely dissolved, and then cellulose nanofiber, ammonium polyphosphate, phosphite, polyethylene glycol terephthalate, polyacrylic acid and nanoalumina are added, and the mixture is stirred and kept warm until uniformly mixed to obtain a polyethylene wax coating liquid.
[0065] Example 12
[0066] The only difference between this embodiment and embodiment 1 is that the ceramic coating includes the following raw materials: 5 g of zirconium oxide powder (particle size 5000 mesh), 2 g of sodium carboxymethyl cellulose, 5 g of polyacrylic acid liquid (analytical grade), and 10 g of styrene acrylic emulsion.
[0067] Example 13
[0068] The only difference between this embodiment and embodiment 1 is that the ceramic coating includes the following raw materials: 12 g of zirconium oxide powder (particle size 5000 mesh), 1 g of sodium carboxymethyl cellulose, 3 g of polyacrylic acid liquid (analytical grade), and 7 g of styrene acrylic emulsion.
[0069] Comparative Example
[0070] Comparative Example 1
[0071] The only difference between this comparative example and Example 1 is that during the preparation of the polyethylene wax coating, an equal amount of polyethylene wax is used to replace the ethylene-vinyl acetate copolymer.
[0072] Comparative Example 2
[0073] The only difference between this comparative example and Example 1 is that during the preparation of the polyethylene wax coating, an equal amount of polyethylene wax is used to replace the cellulose nanofibers.
[0074] Comparative Example 3
[0075] The only difference between this comparative example and Example 1 is that, during the preparation of the polyethylene wax coating, an equal amount of polyethylene wax is used to replace polyacrylic acid.
[0076] Comparative Example 4
[0077] The only difference between this comparative example and Example 1 is that, during the preparation of the polyethylene wax coating, an equal amount of polyethylene wax is used to replace polyethylene glycol terephthalate.
[0078] Performance testing
[0079] The following performance tests were performed on the high-adhesive polyethylene wax composite diaphragms prepared in Examples 1-13 and Comparative Examples 1-4:
[0080] Diaphragm peel strength test:
[0081] Take the diaphragm prepared in each embodiment and comparative example, cut it into 15mm*200mm diaphragm strips, take 15mm wide 3M double-sided tape and stick it on the stainless steel plate, use a roller to roll back and forth twice, then put the ceramic coating side of the diaphragm strip toward the tape, use a roller to roll back and forth 3 times (each time rolling back and forth 10s), and clamp the diaphragm strip vertically and centered in the upper and lower chucks of the tester. The distance between the upper and lower chucks is 100mm, the lower edge of the steel plate is 2mm away from the lower clamp, the test speed is 50mm / min, and the peel strength is tested.
[0082] Thermal stability test:
[0083] The membrane was placed in an oven at 200°C for 1 hour, the dimensional change was detected, and the thermal shrinkage was calculated by the following formula: thermal shrinkage (200°C / 1h) = (pre-dimension - post-baking dimension) / original dimension x 100%.
[0084] The test results are shown in Table 1.
[0085] Table 1
[0086]
[0087] Combining Example 1 and Comparative Examples 1-4 and Table 1, it can be seen that the separator peeling strength of Comparative Examples 1-4 is significantly reduced and the thermal shrinkage is significantly increased compared with Example 1. This shows that the use of the raw material ratio and preparation method of Example 1 helps to reduce the peeling of the polyethylene wax coating in the upper separator from other coatings or base films, and improves the thermal stability of the separator, which helps to improve the durability of the separator.
[0088] It can be seen from Examples 1-13 and Table 1 that the separators of Examples 1-13 have peel strengths greater than 500 N / m and thermal shrinkages less than 1%, which indicates that the raw material ratios and process conditions within the range of Examples 1-13 are conducive to obtaining separators with high adhesion and high thermal stability.
[0089] Moreover, compared with Example 1, the separator peeling strength of Examples 10-11 is significantly increased and the thermal shrinkage is reduced. This shows that the addition of nano-silicon dioxide or nano-alumina helps to further reduce the peeling of the polyethylene wax coating in the upper separator from other coatings or base films and improve the thermal stability of the separator.
[0090] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A high-adhesive polyethylene wax composite diaphragm, characterized in that: The invention comprises a polyethylene wax coating, a ceramic coating and a polyethylene porous base film. The polyethylene wax coating comprises the following raw materials in parts by weight: 50-70 parts of polyethylene wax, 5-15 parts of ethylene-vinyl acetate copolymer, 10-25 parts of reinforcing fiber, 0.5-2 parts of flame retardant, 0.5-2 parts of antioxidant, 2-4 parts of interface compatibilizer and 2-4 parts of polymer containing carboxyl, hydroxyl or amine group.
2. A high-adhesive polyethylene wax composite diaphragm according to claim 1, characterized in that: The interfacial compatibilizer includes at least one of polyethylene terephthalate, polycaprolactone or polyamide elastomer.
3. A high-adhesive polyethylene wax composite diaphragm according to claim 2, characterized in that: The polyethylene wax coating also includes nano silicon dioxide or nano aluminum oxide.
4. The high-adhesive polyethylene wax composite diaphragm according to claim 1, characterized in that: The polymer containing carboxyl, hydroxyl or amine group is any one of polyacrylic acid, polymethacrylic acid, polyvinyl alcohol or polyethyleneimine.
5. A high-adhesive polyethylene wax composite diaphragm according to claim 4, characterized in that: The reinforcing fibers are cellulose nanofibers.
6. The high-adhesive polyethylene wax composite diaphragm according to claim 1, characterized in that: The flame retardant is ammonium polyphosphate or melamine.
7. The high-adhesive polyethylene wax composite diaphragm according to claim 1, characterized in that: The antioxidant is phosphite.
8. The high-adhesive polyethylene wax composite diaphragm according to claim 1, characterized in that: The ceramic coating comprises the following raw materials in parts by weight: 5-12 parts of zirconium oxide powder, 1-2 parts of sodium carboxymethyl cellulose, 3-5 parts of polyacrylic acid liquid, and 7-10 parts of styrene-acrylic emulsion.
9. A method for preparing a high-adhesive polyethylene wax composite diaphragm according to any one of claims 1 to 8, characterized in that: The steps include: Adding polyethylene wax and ethylene-vinyl acetate copolymer into xylene, heating until dissolved, adding reinforcing fiber, flame retardant, antioxidant, interface compatibilizer and polymer containing carboxyl group, hydroxyl group or amine group, mixing evenly, to obtain polyethylene wax coating liquid; Applying the polyethylene wax coating liquid on both sides of the polyethylene porous base film, drying, and forming a polyethylene wax coating by the polyethylene wax coating liquid; The ceramic slurry is coated on the surface of the polyethylene wax coating and dried, so that the ceramic slurry forms a ceramic coating, and the polyethylene wax coating, the ceramic coating and the polyethylene porous base film form a separator for lithium-ion batteries.
10. Application of the high-adhesive polyethylene wax composite diaphragm according to any one of claims 1 to 8 in lithium batteries, characterized in that: The diaphragm of the lithium battery is a high-adhesive polyethylene wax composite diaphragm.
Citation Information
Patent Citations
Aramid fiber coated heat-resistant lithium-ion battery separator and preparation method thereof
CN109904368A
Organic coating / polyethylene composite diaphragm and preparation method thereof and lithium ion battery
CN111192996A
Coated diaphragm and preparation method thereof
CN111326697A
Coating composition for battery diaphragm, composite diaphragm and secondary battery
CN116454540A
Lithium ion battery slurry, diaphragm and lithium ion battery
CN117374514A